2019
DOI: 10.7150/jbji.34072
|View full text |Cite
|
Sign up to set email alerts
|

Commercially available antibiotic-laden PMMA-covered locking nails for the treatment of fracture-related infections - A retrospective case analysis of 10 cases

Abstract: Abstract. Introduction: Fracture-related infections (FRIs) are a devastating complication. FRIs are challenging and should be addressed with a multidisciplinary approach. An FRI should be addressed surgically by non-viable bone debridement, local antibiotic deposition, minimization of dead space and fracture stabilization. Antibiotic-laden PMMA-covered nails are a viable option to face these complications. To demonstrate the safety and utility of commercially available antibiotic-laden PMMA-covered nails, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This provided stability to protect the blood supply, preventing osteonecrosis while delivering local antibiotics to the infection site. This is similar to how antibiotic-coated cement rods have successfully treated intramedullary long bone infections 7,8 .…”
Section: Discussionsupporting
confidence: 68%
“…This provided stability to protect the blood supply, preventing osteonecrosis while delivering local antibiotics to the infection site. This is similar to how antibiotic-coated cement rods have successfully treated intramedullary long bone infections 7,8 .…”
Section: Discussionsupporting
confidence: 68%
“…Local carbapenems, which have been previously shown that they can be safely added to PMMA bone cement, could be a valuable option in these cases [36]. Hence, approaches involving vancomycin and gentamicin, but also carbapenemcarrying bone substitutes, bone cement or coated implants seem reasonable [37][38][39]. However, further studies investigating clinical outcomes, safety for the treated patient and influence of resistance profiles in microbiological environment are required.…”
Section: Local Antibiotic Therapymentioning
confidence: 99%
“…Finally, industry has moved to make bioabsorbable antibiotic coatings 23 and a static, rigid, interlocking nail that comes precoated with a poly D,L-lactic acid matrix impregnated with gentamicin for the use in acute open tibial fractures, aimed to reduce the infection rate in these injuries that have also been described as useful in nonunion treatment. 24–27…”
Section: Discussionmentioning
confidence: 99%